ANALYSIS OF THE DIFFERENCES IN THE INFLUENCE OF FINANCING AND INFLATION ON THE PROFITABILITY OF BANK SHARIA INDONESIA (BSI) BEFORE AND AFTER THE MERGER - Anisa Yulianti; Tenny Badina; Ahmad Fatoni (ZILLZELL MEDIA PRIMA, 2024)
The purpose of this study was to determine the effect of mudharabah, musyarakah, ijarah, murabahah, istishna’, and inflation financing on the profitability of Bank Syariah Indonesia (BSI) before and after the merger. Profitability in this study is measured by return on asset (ROA). This type of research is quantitative and comparative research because this research will compare the effect of bank financing on the financial performance of BSI before and after the merger. The data in this study are time series data and secondary data sourced from OJK, BSI, and Bank Indonesia websites. The data analysis technique used in this study is time series regression, data processing this study using Microsoft Excel and E-views 12 analysis tools. The results stated that mudharabah financing in the long term had a positive effect on BSI profitability before the merger, musyarakah financing, ijarah, murabahah, istishna’, and inflation had no effect on profitability. Meanwhile, in the period after the merger, long-term mudharabah financing had no effect on BSI profitability, musyarakah financing, and inflation had a positive effect on profitability, murabahah, and istishna’ financing had a negative effect on profitability, ijarah financing had no effect on profitability.